Відповідь: Б. √b - √( b - 1 ) .
Пояснення:
4 . √36 < √47 < √49 , тому 6 < √47 < 7 .
В - дь : Б. 6 і 7 .
5 . Якщо b ≥ 1 , то 1/( √b + √( b - 1 ) ) = ( √b - √( b - 1 ) )/[( √b + √( b - 1 ) )X
X( √b - √( b - 1 ) )] = ( √b + √( b - 1 ) )/[( √b )² - ( √( b - 1 ) )² ] =
= ( √b - √( b - 1 ) )/( b - b + 1 ) = √b - √( b - 1 ) .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь: Б. √b - √( b - 1 ) .
Пояснення:
4 . √36 < √47 < √49 , тому 6 < √47 < 7 .
В - дь : Б. 6 і 7 .
5 . Якщо b ≥ 1 , то 1/( √b + √( b - 1 ) ) = ( √b - √( b - 1 ) )/[( √b + √( b - 1 ) )X
X( √b - √( b - 1 ) )] = ( √b + √( b - 1 ) )/[( √b )² - ( √( b - 1 ) )² ] =
= ( √b - √( b - 1 ) )/( b - b + 1 ) = √b - √( b - 1 ) .